ATTAINING THE AUTHENTICITY OF KNOWLEDGE AND THE REVEALED TRUTH COMPREHENSIVELY FROM AL-ZAMAKHSHARI'S PERSPECTIVE - Arroisi, Jarman; Perdana, Martin Putra; Baharudin, Adi Ihza (UIN Kiai Haji Achmad Siddiq Jember, 2023)
Today, humanity is facing the challenge of the authenticity of knowledge. Various efforts have been made to reach the point of truth. However, these efforts have yet to yield optimal results. Therefore, this study aims to address the problem of the search for truth. This study employs descriptive analysis to analyze the attaining of truth that humanity has conducted thus far from al-Zamakhshari's perspective. From this, it is found that modern humans excessively rely on human reason, which is purely empirical; moreover, reason ('aql) plays a role in critical thinking in revealing various phenomena. He also states that reason holds a significant function and role in the Islamic philosophical approach. He asserts that reason is an essential tool for comprehending Revelation and attaining truth: to comprehend the literal and deeper esoteric meaning of the Qur'anic verses and to employ it in interpreting the Qur'an. Al-Zamakhshari also believes that reason plays a crucial role in moral and spiritual life: to enable the differentiation between good and evil and guide individuals towards the right path. Thus, reason becomes a tool to attain the value of truth. Through reason, humans can comprehend the meaning of Revelation, both outwardly and inwardly. It is because truth is not merely physical but also metaphysical; thus, reason must be accompanied by Revelation to attain the meaning of truth. Consequently, reason is the instrument in moral and spiritual life.